Porosity evolution in SnO2 xerogels during sintering under isothermal conditions - Santilli, C. V. [UNESP] (1995)
The structural evolution during isothermal sintering (200≤T≤600 °C) of SnO2 xerogels was studied by small-angle x-ray scattering (SAXS) using synchrotron radiation. The SAXS intensity and, consequently, the structure function of the studied samples exhibit, at low q-wave numbers, a sharp decrease for increasing q, and a characteristic peak at larger q values. We associated these two features to the existence of a bimodal size distribution of electronic density heterogeneities related to (i) interaggregate porosity and (ii) internal microporosity, respectively. The maximum of the peak increases with the sintering time in all studied samples. At 300 °C the q value associated with the maximum intensity remains constant. The data analysis of the set of scattering curves for increasing time intervals at 300 °C is in agreement with Cahn's theory for spinodal decomposition. At higher temperatures, 400-600 °C, the maximum of the structure function increases with time, its position shifts continuously to lower q values, and the value of the integrated intensity in reciprocal space remains constant. The structure function of microporous SnO2 under isothermal treatment in the 400-600 °C range exhibits the dynamical scaling property. The experimental results suggest that the microporosity coarsening is controlled by the coagulation mechanism. © 1995 The American Physical Society.